Solubility of CO2 in Cryogenic Methane: Molecular Dynamics Study - Zhang, Zhi; Li, Qibin; Liu, Chao; Shi, Taihe (Asian Journal of Chemistry, 2013)
It is necessary to estimate the solubility of solids in liquid solvents during cryogenic processes. In this paper, a new approach is presented to calculate CO2 solubility in cryogenic methane by molecular dynamics simulation. The isothermal-isobaric ensemble is employed to simulate the solution system while different CO2 potential models interplay with the LJ sphere of CH4. The classical nucleation theory is referenced to statistic number of solid phase CO2. Ultimately, the solubility of CO2 is the sum of total CO2 to deduct the numbers of CO2 in the solid phase. The results show that LJ and rigid CO2 models are less appropriate for the new method. The flexible models are partly accordance with experimental data.